Pelatihan Manajemen Dana Sosial Berbasis Ta’awuniyah Sebagai Upaya Penguatan SDG’S Pada Majelis Nurul Jalil Bondowoso - Robby Reza Zulfikri; Sebastiana Viphindrartin; Akhmad Munir; Moehammad Fathorrazi; Sjafruddin Sjafruddin (Jurnal Solusi Masyarakat (JSM), 2026)
Majelis Sholawat Nariyah 4444 Nurul Jalil in Jambesari Village, Bondowoso Regency, plays a strategic role in strengthening socio-religious values and collecting community social funds. However, the management of these social funds is still carried out in a simple, manual, and unstructured manner, making it susceptible to commingling funds and lacking transparency. This community service activity aims to enhance the management's understanding and skills in managing social funds transparently, accountably, and sustainably based on ta’awuniyah values while supporting the achievement of Sustainable Development Goals (SDGs). The execution method utilized a community empowerment approach consisting of problem identification, formulation of the Ta'awuniyah Module, social fund management training, practical assistance in financial recording, and evaluation. The results showed an increase in the management's capacity to understand the importance of segregating three types of funds (member savings, assembly cash, and community social funds) and implementing SOPs for fund collection and distribution. Furthermore, the creation of the Ta'awuniyah Module along with simple cash book formats and fund position reports serves as a practical instrument to boost pilgrims' trust. Strengthening social fund governance acts as a foundational step toward encouraging the assembly's economic independence and pioneering the establishment of a cooperative-based Islamic Financial Institution/BMT in the future.